2004
DOI: 10.1074/jbc.m212390200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of G1 Arrest and Apoptosis in Human Jurkat T Cells by Pentagalloylglucose through Inhibiting Proteasome Activity and Elevating p27Kip1, p21Cip1/WAF1, and Bax Proteins

Abstract: Pentagalloylglucose, which is found in many medicinal plants, can arrest the cell cycle at G 1 phase through down-regulation of cyclin-dependent kinases 2 and 4 and up-regulation of the cyclin-dependent kinase inhibitors p27 Kip1 and p21 Cip1/WAF1 in human breast cancer cells. Pentagalloylglucose also induces apoptosis in human leukemic cells. However, the mechanisms by which pentagalloylglucose induces these effects is unclear. We now show that pentagalloylglucose inhibits the activities of purified 20 and 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 60 publications
1
43
0
Order By: Relevance
“…Bax is degraded by the proteasome (8,35) but, like other proteins, needs to be ubiquitinated before it can be processed (specific signaling [21]). Inhibition of the proteasome by specific inhibitors is known to cause an increase in ubiquitinated Bax, and this was shown to slow the rate at which Bax itself can be ubiquitinated (9,30,35,50). Our observations are consistent with such a process but do not identify the nature of the proteasome inhibitor.…”
Section: Discussionmentioning
confidence: 42%
“…Bax is degraded by the proteasome (8,35) but, like other proteins, needs to be ubiquitinated before it can be processed (specific signaling [21]). Inhibition of the proteasome by specific inhibitors is known to cause an increase in ubiquitinated Bax, and this was shown to slow the rate at which Bax itself can be ubiquitinated (9,30,35,50). Our observations are consistent with such a process but do not identify the nature of the proteasome inhibitor.…”
Section: Discussionmentioning
confidence: 42%
“…Cip1 has been intimately linked to turnover of this cdk inhibitor (for a review, see reference 5), although recent studies have questioned this view (8). Whatever the mechanism of p21 Cip1 proteolysis, our data indicate that protein degradation is not a major cause for K cyclin-mediated release of a p21…”
Section: Kim Et Al (18) Observed a Stabilization Of P21mentioning
confidence: 50%
“…The effect of bortezomib on the Bcl-2 family of proteins did not result in a significant change in mitochondrial membrane permeability in the DHL-4 cells at 24 h, but an increase in permeability (due to a decrease in potential) was observed in DHL-7 cells at the higher concentration (25 nmol/L) of bortezomib. Several authors have reported up-regulation of Bax as a result of proteasome inhibition, and cytochrome c release via elevation of Bax proteins has been observed in Jurkat cells (19,20). In MCL cell lines, bortezomib treatment does not result in an overall increase in Bax or Bak expression but conformational changes consistent with their activation are observed (21).…”
Section: Discussionmentioning
confidence: 82%